Le parallélisme dans la poésie Buang - Sankoff, Gillian (Anthropologica, 2022)
The poetic tradition of the Buang (Papua New Guinea) makes extensive use of parallelism. Lexical items placed in parallel constructions can usually be analyzed as sharing at least one trait or feature, and differing in terms of another such feature. Items may even be referentially synonymous, yet differ in terms of a meta-linguistic feature such as foreign language or dialect provenance. Relationships among paired lexical items are analyzed as networks.